PERBANDINGAN TINGKAT KAPASITAS OKSIGEN MAKSIMAL (VO2MAX) TIM FUTSAL BUANA MAS FC DENGAN ASKHARA FC DI SURABAYA - RIZAL RM, ANZA Rizal (Jurnal Prestasi Olahraga, 2013)
In Indonesia futsal sports began to tune about 2003, Although from 1999 to 2000 has started being initiated. This is also evidenced by the increasing number of futsal competition in the country. Starting from the school, and college. One is at a general level or club. In the area of Surabaya there are many futsal teams. Buana Mas and Baskhara are examples futsal team who are in the city of Surabaya. VO2Max plays an important role for the sport of futsal. But more important is not just the amount of VO2Max, but a large percentage of VO2Max use them at sports or games. The percentage of VO2Max is an important factor in inhibiting fatigue from lactic acid buildup in the muscles. Other factors that influence a person or team to achieve the best performance. In the sport of futsal coaching achievement not unlike the sport of football, there are some aspects that must be met, namely aspects of physical fitness training, technical training, tactical training, and mental training. The higher their achievement increasingly complex problems they face. The research objective was to determine VO2Max capacity Buana Mas futsal team and Baskhara futsal team to determine whether or not the comparison of VO2Max significantly between Buana Mas futsal team and Baskhara futsal team. Objectives of this research is Buana Mas futsal team and Baskhara futsal team totaling 30 athletes. Each athlete is composed of 15 players Buana Mas futsal team and 15 players Baskhara futsal team. This study includes the type of quantitative research. Data collection using the Multistage Fitness Test. The results of the study were 1) the average value of VO2max at Buana Mas futsal team by 42.18 and have a Good category at a value of 26.67%. 2) the average value of VO2max at Baskhara futsal team at 40.02 and has a Good category with a value of 20.00%. 3) There were no significant differences between VO2max Buana Mas futsal team and VO2max Baskhara futsal team. Comparison of VO2max between Buana Mas futsal team with Baskhara futsal team with tcount 1.013 <2.145 ttable value. Keywords: Comparison, VO2max, Buana Mas Futsal Team, Baskhara Futsal Team